Memory, politic and ideology: Belmiro, the Proust accent in the capitalism periphery - Fogal, Alex Alves; Araújo, Bárbara Del Rio (Via Atlântica, 2017)
This essay proposal is reflecting how the relations between literature and politic are articulated in O amanuense Belmiro, book that initially was classified psychological and sentimentalist by the literary critique. As on the paradigm from the memorialist novels, following the example of À la recherche du temps perdu, the subjectivity revels, forward the lyrist, the politic and ideological facts, elements indispensable to the aesthetic configuration. On the Cyro dos Anjos novel, the Proust accent conform the local aspects, explicating the most refined memories in the capitalism periphery.